Rheumatic heart disease in the South West region of Cameroon: a hospital based echocardiographic study - Clovis Nkoke; Anastase Dzudie; Christelle Makoge; Engelbert Bain Luchuo; Ahmadou Musa Jingi; Samuel Kingue (BMC Research Notes, 2018)
Abstract Objective Rheumatic heart disease (RHD) prevails as a major public health problem in sub-Saharan Africa. In Cameroon, reports on RHD have been so far limited to a few cities. We sought to describe the demographic, clinical and echocardiographic features of rheumatic heart disease in the Buea Regional Hospital, South West region of Cameroon. Echocardiography reports between June 2016 and June 2017 were reviewed. The diagnosis of RHD was based on the World Heart Federation Criteria for the diagnosis of RHD. Results A total of 669 echocardiograms were performed over the 1 year study period. Twenty-one (3.1%) had a definite echocardiographic diagnosis of RHD. There were 14 (66.7%) females. The age range was 13–94 years with a mean age of 47.8 ± 20.3 years. The most common indications for echocardiography were heart failure (47.6%), and dyspnea (42.9%). The mitral valve was the most commonly affected valve in 80.9% of cases. The most common valve lesion was isolated mitral stenosis (42.9%), followed by isolated mitral regurgitation (28.6%). There were no lesions on the tricuspid and pulmonic valves. Severe lesions were found in 80.9% of the patients. The complications were pulmonary hypertension (66.7%) and atrial fibrillation (9.5%).